Understanding the New Islamic Populism: Al-Mukmin Ngruki Islamic Boarding School - Adibah, Ida Zahara; Mu'aqaffi, Gaffar; Sesarianto, Kevin Ali (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2021)
The emergence of mobilised mass movements, demanding prosperity and the elimination of injustice, has emerged in various parts of the world, without exception in the Middle East and Indonesia. This movement was dominated by educated middle-class youth, sparked the term ummah, and then formed unique solidarity to protest against the government of his country. A new concept is needed by paying attention to the novelty of these characteristics, considering the old populism concept is not relevant enough to explain it. This paper seeks to raise the concept of New Islamic Populism to answer this deficiency. Furthermore, the Al-Mukmin Ngruki Islamic Boarding School (PPIM), the Islamic boarding school often associated with terrorism, is used as the object of research to show the evolution of populism. This study uses qualitative methods and data collection techniques in the form of interviews and literature studies. This study foundthat both santri and ustaz PPIM have aspirations and characteristics, asshown by the New Islamic Populism movement.